Do phosphatase of regenerating liver-3, matrix metalloproteinases-2, matrix metalloproteinases-9, and epidermal growth factor receptor-1 predict response to therapy and survival in glioblastoma multiforme? - Priyanka Soni; Nuzhat Husain; Anil Chandra; Bal Krishan Ojha; Madan Lal Brahma Bhatt; Rakesh Kumar Gupta (Wolters Kluwer Medknow Publications, 2016)
Context: Poor survival of the glioblastoma multiforme (GBM) has been attributed in part to the invasive nature of the lesion making complete surgical removal near impossible. Phosphatase of regenerating liver-3 (PRL-3), matrix metalloproteinases-2 and -9 (MMP-2 and MMP-9), and epidermal growth factor receptor (EGFR-1) play a role in invasive nature of tumor cells. Aims: This study was conducted to evaluate PRL-3, MMP-2, MMP-9, and EGFR-1 (markers) expression in cases to GBM and to correlate their expression with therapy response and survival. Settings and Design: GBM cases (n = 62) underwent surgery followed by radiation (n = 34) and chemoradiation (n = 28). Using WHO Response Evaluation Criteria in Solid Tumors criteria response to therapy was assessed at 3 months and cases followed up for survival. Subjects and Methods: Expression of markers was assessed by immunohistochemistry as a percentage of positive tumor cells in hot spots. Statistical Analysis Used: Kaplan-Meier, ANOVA, Chi-square test, univariate, and multivariate Cox-regression analysis was done. Results: Response to therapy was evident in 54.8% cases of responders with the mean survival of 494.03 ± 201.13 days and 45.2% cases of non responders (278.32 ± 121.66 days) with P = 0.001. Mean survival for the patient's opted chemoradiation was 457.43 ± 222.48 days which was approximately 3 months greater than those who opted radiation alone (P = 0.029). We found PRL-3 overexpression was an independent, significant, poor prognostic factor for survival by multivariate analysis (P = 0.044). Cases negative for MMP's and EGFR showed increased survival, but the difference was insignificant. Conclusion: PRL-3 expression appears to be related to an adverse disease outcome.